Proceedings of the 1st UPY International Conference on Education and Social Science (UPINCESS 2022) 2022
DOI: 10.2991/978-2-494069-39-8_6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Budget Performance with Value for Money Concept

Abstract: This study aims to examine the-impact of accountability, transparency, and oversight on-budget performance. The type of data used in this research is quantitative. This research was conducted using a questionnaire survey conducted by the Regional Device Unit in Bantul Regency. The object of this research is all employees of regional organizations. The sample of this study was 40 respondents who participated in the preparation of the budget. The method used to determine the sample is purposive sampling. Data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…For instance, Gemmell et al (2015) examined the impacts of GDP on changes in total government expenditure, alongside changes in the shares of spending devoted to various categories. While Nusron et al (2022) examined the impact of three predictor variables, namely: accountability, transparency, and oversight on-budget performance. Similarly, Pramudiati et al (2023) concluded that the better the accountability, transparency and supervision, the better of budget performance based on the findings that accountability, transparency, and supervision positively influence the performance of the value for money concept budget.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Gemmell et al (2015) examined the impacts of GDP on changes in total government expenditure, alongside changes in the shares of spending devoted to various categories. While Nusron et al (2022) examined the impact of three predictor variables, namely: accountability, transparency, and oversight on-budget performance. Similarly, Pramudiati et al (2023) concluded that the better the accountability, transparency and supervision, the better of budget performance based on the findings that accountability, transparency, and supervision positively influence the performance of the value for money concept budget.…”
Section: Introductionmentioning
confidence: 99%